2021
DOI: 10.1111/cch.12917
|View full text |Cite
|
Sign up to set email alerts
|

Human (in)security and psychological well‐being in Palestinian children living amidst military violence: A qualitative participatory research using interactive maps

Abstract: Background: Research has widely evidenced the effects of war and political violence on the functioning of children, with a great accord in diagnosing children's psychological burdens related to their exposure to violence. Yet, within this literature, the influence of the chronic sense of insecurity on their psychological functioning during and after hostilities remains unexplored.Methods: The present study aimed at exploring interrelated relationships between the perceived insecurity and the children's psychol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 70 publications
1
7
0
Order By: Relevance
“…A sense of safety was a foundation for other opportunities. This is consistent with studies that have found that feeling safe is a key protective factor for refugees' resilience [14,22]. Our participants felt that the Netherlands provided a great deal of opportunities, especially for those who have mastered the language.…”
Section: Societal Level Factorssupporting
confidence: 91%
See 1 more Smart Citation
“…A sense of safety was a foundation for other opportunities. This is consistent with studies that have found that feeling safe is a key protective factor for refugees' resilience [14,22]. Our participants felt that the Netherlands provided a great deal of opportunities, especially for those who have mastered the language.…”
Section: Societal Level Factorssupporting
confidence: 91%
“…Studies on Palestinian refugee children in Gaza and West Bank have pointed to risk factors, including poverty, violence, and marginalization, and key protective factors like youth education, supportive relationships, and social participation [13]. Moreover, feelings of insecurity from the social environment have been found to affect Palestinian children's mental health and psychological functioning [14]. Research on refugees and asylum seekers in transitional countries has identified social support, cognitive strategies, education and training opportunities, employment and economic activities, behavioral strategies, political advocacy, environmental conditions, religion, and spirituality as the factors promoting their well-being [15].…”
Section: Introductionmentioning
confidence: 99%
“…Transformative collective healing experiences rise from critical consciousness processes that augment three generations' awareness about their rights and opportunities and the systematic violations of their rights. Accordingly, interventions informed by human rights and human security approaches might be more efficient and effective in answering needs across generations of refugees when operating in a context of structural and settler-colonial violence, such as the occupied Palestinian territories (Diab et al, 2018(Diab et al, , 2022Veronese et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, Veronese et al ( , 2022 underlined refugee children's capabilities and survival skills as a source to react to the ongoing trauma and mobilize sources of agency. Namely, children could reshape their surrounding environment, giving sense to their lives through daily acts of love, decency, familial intimacy, and play, reaffirming their rights or resisting for existing .…”
Section: Introductionmentioning
confidence: 99%
“…Like our findings, community support included both formal provisions of resources and informal mechanisms of establishing connections, friendships, and opportunities for shared experiences. Veronese and colleagues (2021) looked at risk and protective factors that predicted the psychological well‐being and adjustment to the trauma of 75 Palestinian refugee children. Their findings emphasized the importance of safe environments, connection to family and community, and maintaining a strong identity amid forces of oppression as predictors of well‐adjustment.…”
Section: Discussionmentioning
confidence: 99%